Karta si︠e︡vernoĭ chasti Onezhskago ozera sostavlena po opisi 1877, 81-84 gg. / Izdana Gidrograficheskimʺ Departmentomʺ Morskago Ministerstva vʺ 1886 godu - Russia. Gidrograficheskīĭ departament (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департмент, 1885)
Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; Pulkovo meridian.; "N-i︠a︡ Chastʹ Onezhskago Ozera" [Northern Part of Lake Onega] -- across top margin.; "Masshtabʺ: 2 versty (100 sazh.) vʺ di︠u︡ĭmi︠e︡ - 1/84000." [Scale: 2 versts (1000 sazhens) in 1 inch - 1/84000].; "No. 171" -- handwritten bottom right margin Grayscale; 1:84,000